Response of Neem Leaves Azadirchta indica Extract Immune System of (Oreochromis niloticus) - Lutfi Hamzan Wari; Ayu Adhita Damayanti; Fariq Azhar (Airlangga University, 2020)
Tilapia (Oreochromis niloticus) is a species of freshwater fish that is widely cultivated in areas that have a large quantity of fresh water. In the cultivation of tilapia fish are often infected by fish diseases which not infrequently thwart the growth and survival of fish resulting in death of fish that are cultivated (crop failure). This study aims to analyze the response of giving neem leaf extract (Azadiracta indicida) to the immune system and growth of tilapia. The fish were given neem leaf extract which was added to the feed for 45 days in 54cm x 37cm x 29cm containers each with 10 heads / container with a volume of 20 liters. The study was conducted in 5 treatments, control + (commercial feed and infected by Aeromonas hydrophila 106 cfu / ml as much as 0.1 ml / head), control - (commercial feed of bacterial infection), P1 (feed mixed with 0.5% extra neem leaves and infected with bacteria ), P2 (1% extracted and infected), P3 (2% extracted and infected). The results showed that administration of neem leaf extract at a dose of 1% was able to maintain SR by 100%, increasing the number of erythrocyte tilapia by 15.0 í— 105 cells / ml and leukocytes by 15.0 í— 104 cells / ml and hemoglobin by 6.0 % of the total blood cells contained in P4 that play a role in the immune system of tilapia. Based on the results of this study, neem leaf extract can be used in tilapia aquaculture as an immunostimulant because it can improve survival, red blood cells, white blood cells and hemoglobin.Keyword : Extract neem leaves, Aeromonas hydrophila, Tilapia, Feed.